THE ENIGMA OF PAKISTAN'S NUCLEAR DETERRENCE: AN ALTERNATE PERSPECTIVE (Margalla Papers, 2024)
Pakistan has developed its nuclear and missile programmes primarily in response to perceived threats from India. Pakistani officials claim that these capabilities are for self-defence, aiming to deter India from initiating a war. However, Indian military strategists have consistently explored options to overcome these deterrent measures. Applying the theoretical models of the “Concept of Deterrence”, “Agreed Battles”, and “Iterated Game Theory”, existing gaps in Pakistan's understanding and projection of deterrence against India, coupled with its displayed behaviour, have been analysed. It has been found that the current pattern is bolstering confidence in the Indian leadership that the application of military instruments against Pakistan is possible and will achieve political goals. The key to addressing this issue lies in Pakistan, recognising that deterrence is ongoing. Effectively managing nuclear deterrence involves a strategic interplay of intent, capability, and communication, with a crucial emphasis on continual adaptation to maintain effectiveness. Bibliography EntryAmin, Aezaz Aizad. 2024. "The Enigma of Pakistan's Nuclear Deterrence: An Alternate Perspective." Margalla Papers 28 (1): 109-122.